The Efficacy of Composite Essential Oils against Aflatoxigenic Fungus Aspergillus flavus in Maize - Fangzhi Xiang; Qianqian Zhao; Kai Zhao; Hao Pei; Fang Tao (Toxins, 2020)
The efficacy of eleven essential oils (EOs) against Aspergillus flavus NRRL 3357 was investigated. The highest antifungal activity against this aflatoxigenic fungus was exhibited by cinnamon, oregano and lemongrass, which showed low minimum inhibitory concentration (MIC) values under vapor conditions. Interactions of the three EOs were evaluated by the fractional inhibition concentration index (FICI), and the composite essential oils (CEO) showed synergistic inhibitory activities. Chemical analysis of the composite essential oils of cinnamon, oregano, and lemongrass (COL-CEO) revealed that (Z)-citral (33.44%), (E)-citral (32.88%) and carvacrol (19.84%) were the dominant components, followed by limonene (4.29%) and cinnamaldehyde (3.76%). COL-CEO not only inhibited fungal growth but also decreased aflatoxin B1 production by A. flavus. Downregulation of the relative expression of aflatoxin genes in the aflatoxin biosynthetic pathway by COL-CEO revealed its anti-aflatoxigenic mechanism. COL-CEO could also affect the colonization of A. flavus on maize grains. Therefore, COL-CEO may be considered as a potential natural antifungal agent, which could be used for the storage of maize and other grains.